Evacuation Model of Earthquake in Multi-Storey Building using 3D GIS and Agent-Based Model - Nisaa', Ratri Ma'rifatun; Nurmaya, Acintya; Wardana, Randy Alihusni; Arifati, Azmiyatul (Indonesian Journal of Geography, 2025)
Evacuation simulations in multi-storey building using 3D GIS and ABM require further study. Existing models lack comprehensive input on various building attributes. This research aims to develop a model for simulating earthquake evacuations in multi-storey buildings. The building and its occupants (agents) are modeled in detail, with building dimensions and designs obtained through measurements and field surveys. A field observation was conducted to determine agent's distribution. Agents placed in the building model are given certain behaviors once evacuation begins. The research focuses on a multi-storey building at Universitas Gadjah Mada (UGM). The model can assess the effectiveness of current evacuation facilities. Computer simulation results show that 266 agents require 140.8 seconds to evacuate, with no bottleneck observed at any location. A guest agent, assumed to lack knowledge of the building’s emergency information, is observed to exit last. In contrast, the fastest evacuation is achieved by agents familiar with the building, represented by a group of lecturers/staff. Model validation, through comparison with a drill simulation, shows a time difference of 0.45 seconds. Findings indicate that, under current scenarios, the building’s evacuation facilities have adequate capacity.